Supply chain business intelligence: model proposal and implementation to support the online sales supply chain end to end operation of a portuguese electronics retail company - Freire, Marcela Alves (2020)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence